?STUDIES ON THE PROTEOLYTIC ACTIVITY OF PAPAYA JUICE ? (Biological Sciences - PJSIR, 1998)
The activity of proteases in crude papaya juice Carrica papaya was studied by using casein as a substrate. The activityof enzyme in papaya juice was optimum at pH 8.0 and temperature 80-85°C. The crude juice was heat stable andexhibited about 8-10 fold increase in activity at 85°C. Cysteine hydrochloride and sodium cyanide showed a markedactivating effect at optimum temperature.